Virologic outcome among patients receiving antiretroviral therapy at five hospitals in Haiti - Jean Louis, Frantz; Buteau, Josiane; François, Kesner; Hulland, Erin; Domerçant, Jean Wysler; Yang, Chunfu; Boncy, Jacques; Burris, Robert; Pelletier, Valerie; Wagar, Nicholas; Deyde, Varough; Lowrance, David W.; et al. (PloS one, 2018)
Viral load (VL) assessment is the preferred method for diagnosing and confirming virologic failure for patients on antiretroviral therapy (ART). We conducted a retrospective cross-sectional study to evaluate the virologic suppression rate among patients on ART for ≥6 months in five hospitals around Port-au-Prince, Haiti. Plasma VL was measured and patients with VL <1,000 copies/mL were defined as virologically suppressed. A second VL test was performed within at least six months of the first test. Factors associated with virologic suppression were analyzed using logistic regression models accounting for site-level clustering using complex survey procedures. Data were analyzed for 2,313 patients on ART for six months or longer between July 2013 and February 2015. Among them, 1,563 (67.6%) achieved virologic suppression at the first VL test. A second VL test was performed within at least six months for 718 (31.0%) of the patients. Of the 459 patients with an initial HIV-1 RNA <1,000 copies/mL who had a second VL performed, 394 (85.8%) maintained virologic suppression. Virologic suppression was negatively associated with male gender (adjusted odds ratio [aOR]: 0.80, 95% CI: 0.74-0.0.86), 23 to 35 months on ART (aOR:0.72[0.54-0.96]), baseline CD4 counts of 201-500 cells/mm3 and 200 cells/mm3 or lower (aORs: 0.77 [0.62-0.95] and 0.80 [0.66-0.98], respectively), poor adherence (aOR: 0.69 [0.59-0.81]), and TB co-infection (aOR: 0.73 [0.55-0.97]). This study showed that over two-thirds of the patients in this evaluation achieved virologic suppression after ≥ six months on ART and the majority of them remained suppressed. These results reinforce the importance of expanding access to HIV-1 viral load testing in Haiti for monitoring ART outcomes.